Neuromyelitis Optica Spectrum Disorder (NMOSD) or Chronic-Relapsing Inflammatory Optic Neuropathy (CRION)?: A Challenge in Diagnosis and Treatment: Poster Presentation - Case Report - Ophthalmologist - Alia Arianti, MD (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Neuromyelitis optica spectrum disorder (NMOSD) is a chronic inflammatory, immune-mediated central nervous system disease targeting the AQP4-water channel membrane protein of the optic nerve and the spinal cord. This case report aims to present a case of seroconverting NMOSD which was initially diagnosed as chronic relapsing inflammatory optic neuropathy (CRION). Case Illustration : 15-year-old female with recurrent, steroid-dependent optic neuritis of the LE. During the first attack, brain MRI showed optic nerve inflammation with normal brain findings. Initial test for AQP4-IgG, MOG-Ab and ANA profile were negative. The diagnosis of CRION was made. Treatment with corticosteroid and immunosuppressant agent was maintained for one year. After treatment cessation, however, LE optic neuritis recurred with bilateral lower limb weakness. Spinal MRI showed signs of longitudinal extensive transverse myelitis. Re-testing for AQP4-IgG showed positive result. Diagnosis of NMOSD was made, and the patient was treated with high-dose intravenous corticosteroid followed by oral dose, and immunosuppressant. Final visual acuity of the LE was 1.0, with minimal residual visual field defect and good motor function. Discussion : During the initial attack, the patient did not meet the 2015 NMOSD international consensus diagnostic criteria. The AQP4-IgG was negative and no other corresponding signs and symptoms. The criteria was met one year after: optic neuritis, LETM and positive seroconversion of AQP4-IgG. Conclusion : Diagnosing NMOSD is at times challenging especially during initial attack. Retesting of the AQP4- IgG is at times necessary in seronegative patients, especially in children showing ADEM-like event with optic neuritis and LETM to achieve diagnosis and proper treatment strategy.